(untitled) (Al-Academy, 2023)
The current research (technical mediator in contemporary Iraqi painting) dealt with the concept of technical mediator in contemporary arts and its role in the qualitative transformation in art, the diversity of discoveries in technical media that artists use in their artistic achievement, and the extent of their impact on contemporary Iraqi painting, where the research problem was identified (what is The nature and role of technical media in showing works in contemporary Iraqi painting) and (What are the intellectual and aesthetic concepts of media and techniques as references for contemporary art in Iraq). The second topic dealt with technical media and their impact on the plastic arts, and the third topic focused on the technical medium and the mechanisms of its manifestation in contemporary Iraqi painting, and the third chapter, which included samples of the sample numbered (3), was a model representing the work of three Iraqi artists, while the fourth chapter included the results of the research. And conclusions, and sealed by the researcher sources and references.Conclusions: -1. Achieving visual creativity in artistic works by experimenting with contemporary media and techniques.2. The clear influence of contemporary Western techniques, in the use of new non-circulated media, as a result of constant friction with the latest prevailing artistic trends.3. Contemporary media and techniques are clearly influential in the Iraqi plastic achievement through the dismantling of forms, giving expression a dramatic dimension, and modifying the media from its relations to become self-sufficient, starting towards innovation and singularity in the constructivist style.4. The Iraqi artist was tempted to experiment according to contemporary propositions, after he was tired of the traditional ideas and methods, which have become stagnant in a vicious circle.5. The works of the three artists (Kuish, Abdeen, Bilal) were distinguished by the freedom to choose the appropriate media for their work, and to try to dialogue with the other through multimedia to convey the suffering of his people and the crises they are going through